Monitoramento sorológico para diagnóstico precoce da aspergilose em pinguins em cativeiro - Cabana, Ângela Leitzke (2013)
Aspergillosis is a leading cause of death in captive penguins. Though being a known problem for decades, most reported cases are still only confirmed in post-mortem examinations, requiring further studies on methods for in vivo diagnosis of the disease. This study aimed to evaluate the efficacy of detection of anti-Aspergillus fumigatus antibodies through the performance by serological monitoring with agar gel double radial immunodiffusion (AGID) for in vivo diagnosis of aspergillosis in captive penguins. The study was performed including Magellanic penguins in a rehabilitation program at Center for Recovery of Marine Animals (CRAM/FURG) in the period from 2009 to 2011. We included 134 Magellanic penguins (Spheniscus magellanicus) in rehabilitation at CRAM, which were monitored by AGID weekly until its final destination (death or release) totaling 660 studied serum samples. The serological monitoring was performed in order to detect anti-Aspergillus fumigatus antibodies using commercial antibodies and antigen. All animals were clinically monitored and post-mortem examinations were performed on penguins that died during the study period. A total of 28% (37/134) penguin died, 89.2% (33/37) of aspergillosis, 11% (4/37) of other causes and 97 were released. From the 33 animals with proven aspergillosis, 21 had anti-A. fumigatus antibodies by AGID, being the average interval between death and the positive AGID result of 16.4 days. Twelve seronegative animals eventually died of aspergillosis. The rates of sensitivity and specificity were 63.6% and 95%, respectively, and positive and negative predictive values were 80.7% and 88.9% respectively. These data demonstrate that serological monitoring for the detection of antibodies by AGID may be a useful and important tool for the diagnosis of aspergillosis in penguins. As our study with AGID in penguins is pioneer, more studies are required concerning the prognosis in cases of aspergillosis in penguins whose therapeutic intervention is based on diagnosis by AGID, considering that the average period between the positive result of this test and the death of the animal was less than one month. Key-words: Sphenisciformes. Captivity